Persepsi Santri dan Kiai terhadap Pluralisme Agama di Pendidikan Ulama Tarjih Muhammadiyah (PUTM) dan Aswaja Nusantara Yogyakarta - Arifin, Zainal; Yu’timaalahuyatazaka, Yu’timaalahuyatazaka (IAIN Ponorogo, 2017)
Abstract: There are the controversies of religious pluralism in the pluralistic society context in Nusantara (Indonesia). Even, it evokes some conflicts such as war of ideas. This article focused on the perspectives of Kiai and Student Muhammadiyah and NU on the religious pluralism through education practices in the PUTM dan Aswaja Nusantara Boarding School. Both of them are considered representative because they contain the concept, ideas, and paradigms of Muhammadiyah and NU. This is a qualitative research, the data obtained from interviews and literature study by giving each verification, correction and complementary. The result of this research, The PUTM perspective of pluralism is regarding to it as a social reality that responded positively and constructively. While, Aswaja Nusantara prioritizes a dialectics amongst to social reality, local culture, and a strong Islamic tradition. Nonetheles, both of them have a same concept to strengthen their faith (akidah) by using exclusivism to refuse the theological concept of religious pluralism, but accepted the sociological concept of religious pluralism.Ø§Ù„Ù…Ù„Ø®Øµ: ÙƒØ§Ù† Ø§Ù„ØØ¯ÙŠØ« Ø¹Ù† Ø§Ù„ØªØ¹Ø¯Ù‘Ø¯ÙŠØ© Ù„Ø§ ÙŠØ²Ø§Ù„ Ø¸Ø§Ù‡Ø±Ø§ ÙÙŠ Ø³ÙŠØ§Ù‚ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…ØªØ¹Ø¯Ø¯ ÙÙŠ Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§. ÙˆÙƒØ«ÙŠØ±Ø§ Ù…Ø§ ÙŠØ¤Ø¯Ù‘Ù‰ Ù‡Ø°Ø§ Ø¥Ù„Ù‰ Ø§Ù„Ù†Ø²Ø§Ø¹ Ø§Ù„ÙÙƒØ±ÙŠÙ‘. ÙˆØ§Ù„Ø´ÙŠØ¡ Ø§Ù„Ø¬Ø§Ø°Ø¨ Ù‡Ùˆ Ø§Ù„Ù†Ø¸Ø± Ø¥Ù„Ù‰ ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø¹Ù„Ù…Ø§Ø¡ ÙˆÙ…ØªØ¹Ù„Ù…ÙŠ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù„Ø¬Ù…Ø¹ÙŠØ©